Model of Supervision of Unregistered Community Organisations in Order to Realise Legal Certainty in Indonesia - Dyanata, Nandu; Budiono, Abdul Rachmad; Anshari, Tunggul; Djatmika, Prija (Universitas Negeri Semarang, 2024)
As social creatures, humans have a tendency to live in society and organise their lives, which is guaranteed by the constitution, which provides guarantees for association and organisation. This freedom has implications where currently there are many community organisations that exist with various objectives, the existence of community organisations themselves in the country has been far more advanced in its work to empower the community. The problem is that CSOs currently have two forms, namely registered and unregistered, so there are problems in supervision. The variety of mass organisations gave birth to various groups, one of which was based on religious ideology, such as Hizbut Tahrir Indonesia (HTI) which was dissolved on 19 July 2017. The Law on Mass Organisations affirms the principles that must be used in the establishment of mass organisations, one of the prohibitions is that mass organisations must not conflict with Pancasila and the 1945 Constitution. However, there is no definite formulation regarding the indicators of being contrary to Pancasila or Anti- Pancasila. Various restrictions are displayed in the form of prohibitions that show the existence of the existence of a mass organisation law. However, the application of the law should have a balance of inherent matters, namely between rights and obligations.